Treatment of Pediatric Sternotomy Wound Complications: A Minimally Invasive Approach - Jo, Taehee; Hur, Joon; Kim, Eun Key (The Thoracic and Cardiovascular Surgeon, 2021)
Background Pediatric sternal wound complications (SWCs) include sterile wound dehiscence (SWD) and superficial/deep sternal wound infections (SSWI/DSWI), and are generally managed by repetitive debridement and surgical wound approximation. Here, we report a novel nonsurgical management strategy of pediatric sternotomy wound complications, using serial noninvasive wound approximation technique combined with single-use negative pressure wound therapy (PICO) device.Methods Nine children with SWCs were managed by serial approximation with adhesive skin tapes and serial PICO device application. Thorough surgical debridement or surgical approximations were not performed.Results Three patients were clinically diagnosed as SWD, two patients as SSWI, and four patients as DSWI. None of the wounds demonstrated apparent mediastinitis or bone destructions. PICO device was applied at 16.1 days (range: 6–26 days) postoperatively, together with serial wound approximation by skin tapes. The average duration of PICO use was 16.9 days (range: 11–29 days) and the wound approximation was achieved in all patients. None of the patients underwent aggressive surgical debridement or invasive surgical approximation by sutures.Conclusion We report our successful management of selected pediatric SWCs, using serial noninvasive wound approximation technique combined with PICO device.
Keywords: wound healing; wound infection; surgery; complications; sternum